The effect of cooling procedures on monomer elution from heat-cured polymethyl methacrylate denture base materials - Nick POLYCHRONAKIS; Maria DIMITRIADI; Gregory POLYZOIS; George ELIADES (University of São Paulo, 2022)
Abstract Objective To evaluate the amount of methyl methacrylate (MMA) released in water from heat-cured polymethyl methacrylate (PMMA) denture base materials subjected to different cooling procedures. Methodology Disk-shaped specimens (Ø:17 mm, h:2 mm) were fabricated from Paladon 65 (PA), ProBase Hot (PB), Stellon QC-20 (QC) and Vertex Rapid Simplified (VE) denture materials using five different cooling procedures (n=3/procedure): A) Bench-cooling for 10 min and then under running water for 15 min; B) Cooling in water-bath until room temperature; C) Cooling under running water for 15 min; D) Bench-cooling, and E) Bench-cooling for 30 min and under running water for 15 min. A, B, D, E procedures were proposed by the manufacturers, while the C was selected as the fastest one. Control specimens (n=3/material) were fabricated using a long polymerization cycle and bench-cooling. After deflasking, the specimens were ground, polished and stored in individual containers with 10 ml of distilled water for seven days (37oC). The amount of water-eluted MMA was measured per container using isocratic ultra-fast liquid chromatography (UFLC). Data were analyzed using Student's and Welch's t-test (α=0.05). Results MMA values below the lower quantification limit (LoQ=5.9 ppm) were registered in B, C, E (PA); E (PB) and B, D, E (QC) procedures, whereas values below the detection limit (LoD=1.96 ppm) were registered in A, D (PA); A, B, C, D (PB); C, D, E (VE) and in all specimens of the control group. A, B (VE) and A, C (QC) procedures yielded values ranging from 6.4 to 13.2 ppm with insignificant differences in material and procedure factors (p>0.05). Conclusions The cooling procedures may affect the monomer elution from denture base materials. The Ε procedure may be considered a universal cooling procedure compared to the ones proposed by the manufacturers, with the lowest residual monomer elution in water.